# UNIT 2: SOLVING EQUATIONS AND INEQUALITIES SOLVE EACH OF THE FOLLOWING EQUATIONS FOR y. # 1. - 2 x + 5 y = 15 + 2 x 5 y = 2 x + 15 55 y = 2 x + 15 5 y.

## Presentation on theme: "UNIT 2: SOLVING EQUATIONS AND INEQUALITIES SOLVE EACH OF THE FOLLOWING EQUATIONS FOR y. # 1. - 2 x + 5 y = 15 + 2 x 5 y = 2 x + 15 55 y = 2 x + 15 5 y."— Presentation transcript:

UNIT 2: SOLVING EQUATIONS AND INEQUALITIES SOLVE EACH OF THE FOLLOWING EQUATIONS FOR y. # 1. - 2 x + 5 y = 15 + 2 x 5 y = 2 x + 15 55 y = 2 x + 15 5 y = 2 / 5 x + 3

UNIT 2: SOLVING EQUATIONS AND INEQUALITIES SOLVE EACH OF THE FOLLOWING EQUATIONS FOR y. # 2. 2 x + y + 1 = 0 - 2 x y + 1 = - 2 x - 1 y = - 2 x – 1

UNIT 2: SOLVING EQUATIONS AND INEQUALITIES SOLVE EACH OF THE FOLLOWING EQUATIONS FOR y. # 3. - x – 6 y = 30 + x - 6 y = x + 30 - 6 y = - x - 30 6 y = - 1 / 6 x – 5

UNIT 2: SOLVING EQUATIONS AND INEQUALITIES SOLVE EACH OF THE FOLLOWING EQUATIONS FOR y. # 4. 9 x = 9 y + 36 - 36 9 x = 9 y + 36 - 36 9 x – 36 = 9 y 99 x – 4 = y

UNIT 2: SOLVING EQUATIONS AND INEQUALITIES SOLVE EACH OF THE FOLLOWING EQUATIONS FOR y. # 5. 5 x – 3 y = 0 - 5 x - 3 y = - 5 x - 3 y = 5 / 3 x

UNIT 2: SOLVING EQUATIONS AND INEQUALITIES SOLVE EACH OF THE FOLLOWING EQUATIONS FOR y. # 6. y – 4 = - 3 + 4 y = 1

UNIT 2: SOLVING EQUATIONS AND INEQUALITIES SOLVE EACH OF THE FOLLOWING EQUATIONS FOR y. # 7. 4 x + 5 y = 5 - 4 x 5 y = - 4 x + 5 55 y = - 4 / 5 x + 1

UNIT 2: SOLVING EQUATIONS AND INEQUALITIES SOLVE EACH OF THE FOLLOWING EQUATIONS FOR y. # 8. 3 x – 8 = y – 4 + 4 3 x – 4 = y

UNIT 2: SOLVING EQUATIONS AND INEQUALITIES SOLVE EACH OF THE FOLLOWING EQUATIONS FOR y. # 9. 20 y – 60 = 5 x + 60 20 y = 5 x + 60 20 y = 5 / 20 x + 60 / 20 y = 1 / 4 x + 3

UNIT 2: SOLVING EQUATIONS AND INEQUALITIES SOLVE EACH OF THE FOLLOWING EQUATIONS FOR y. # 10. - 2(x + y) = 2 + 5 x - 2 x – 2 y = 2 + 5 x + 2 x – 2 y = 7 x + 2 - 2 y = - 7 / 2 x – 1

UNIT 2: SOLVING EQUATIONS AND INEQUALITIES SOLVE EACH OF THE FOLLOWING EQUATIONS FOR y. # 11. x + y = 5 – x - x y = - 2 x + 5

UNIT 2: SOLVING EQUATIONS AND INEQUALITIES SOLVE EACH OF THE FOLLOWING EQUATIONS FOR y. # 12. x + y = 2 y – 5 - y x = y – 5 + 5 x + 5 = y

Similar presentations